2017
DOI: 10.1084/jem.20161759
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent rhinovirus infections in a child with inherited MDA5 deficiency

Abstract: Human MDA5 deficiency features recurrent severe human rhinovirus (HRV) infections. MDA5 serves a protective and nonredundant role in protecting against HRV in the respiratory tract, through its effects on virus sensing and triggering of antiviral IFN signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(118 citation statements)
references
References 84 publications
(103 reference statements)
5
110
1
2
Order By: Relevance
“…While the revised version of this paper was under review, an independent study showed an association between IFIH1 deficiency and life-threatening infections with HRV and other respiratory viruses in a child carrying another homozygous missense IFIH1 variant (24). This observation further supports a causal role for IFIH1 deficiency in extreme susceptibility to common respiratory viruses.…”
Section: Discussionmentioning
confidence: 67%
“…While the revised version of this paper was under review, an independent study showed an association between IFIH1 deficiency and life-threatening infections with HRV and other respiratory viruses in a child carrying another homozygous missense IFIH1 variant (24). This observation further supports a causal role for IFIH1 deficiency in extreme susceptibility to common respiratory viruses.…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, pollen exposure reduces the expression of MDA5, and MDA5 deficiency can predispose to recurrent rhinovirus infections. 39 Furthermore, exposure to pollen resulted in a reduced translocation of phosphorylated IRF3 and IRF7 into the nucleus following activation by double-stranded RNA suggesting a mechanistic link between pollen exposure, reduction in enhanceosome complexes and reduced CCL5 and IFN-λ release. IRF3 has also been shown to play a role in triggering apoptosis, a defense mechanism of virally infected cells to reduce viral load and replication and thus prevent spreading of the infection.…”
Section: Discussionmentioning
confidence: 95%
“…However, contrary to published reports, we observed several episodes of severe viral infections in one patient, suggesting the possibility that JAK inhibitors might significantly increase the risk of infections possibly in cases of more severe lung involvement or in the presence of genetic modifiers, not investigated in our patient, with consequent deterioration of t he lung disease. Interestingly, the most frequent virus isolated was rhinovirus, which may be a direct consequence of effective type I IFN inhibition by ruxolitinib at least in respiratory epithelial cells, where IFN-β is required to control rhinovirus [16,17]. On the other end, these infections might result from a cumulative effect of the drug with the reported developmental and in vitro proliferative defects of STING mutant T lymphocytes [18,19].…”
Section: Discussionmentioning
confidence: 99%